Efeito longitudinal de tratamentos de superfície modificados por Nd:YAG laser na permeabilidade dentinária - Esteves, Stella Renata Machado Silva [UNESP] (2013)
Dentin hypersensitivity affects a large population and generates a lot of discomfort. Most treatments are based on the use of agents to reduce permeability with their effect related to individual factors and with low longevity. The aim of this study was to evaluate in vitro the efficacy and longevity of treatments for reducing dentin permeability, such as fluoride, adhesives and collagen deproteinization, associated or not with Nd : YAG laser by measuring the dentinal fluid flow in a permeability machine ( Odeme , Brazil). Seventy bovine dentin specimens of 6mm diameter and 1 mm thickness were divided into 7 groups according to treatment: Group C: control without treatment; Group F: fluoride varnish; Group FL: fluoride varnish + Nd:YAG laser, Group A: Scotchbond Universal, Group AL: adhesive + Nd:YAG laser, Group D: 10 % NaOCl + adhesive; group DL: 10 % NaOCl, adhesive + Nd:YAG laser. The specimens had dentin permeability measured in 4 phases: in the presence of the occlusal smear layer (Minimum Permeability), after EDTA application for 1 min (Maximum Permeability), after the treatments and after erosion / abrasive challenge; in order to analyze the effectiveness and durability of each treatment. RM ANOVA (2 factors) and Tukey (α = 0,05) were applied. Treatments were effective in reducing permeability except for group FL; the laser treatments were associated with significant reduction in permeability, except for the FL group; group AL was the most effective treatment in the immediate post-treatment analysis and; the DL group was the most effective post- challenge (longitudinal). We conclude that only the DL treatment was effective longitudinally